Synthesis, Characterization, and Biological Evaluation of Chromium(III) Complexes of Alanine and Valine - Shuaibu Musa; Suleiman Ola Idris; David A. Onu; Ahmed B. Suleiman (Hamadan University of Medical Sciences, 2019)
Two metal-amino acid complexes, Cr(III)-alanine and Cr(III)-valine, were synthesized and characterized by IR spectroscopy, powder X-ray diffraction (XRD) analysis, magnetic susceptibility, and molar conductivity measurements. Molar conductivity measurements indicated that the composition of the metal complexes corresponds to a metal-amino acid ligand ratio of 1:3. The IR spectra indicated that the amino acids act as bidentate ligands with coordination involving the carboxyl oxygen and the nitrogen of the amino group. Magnetic susceptibility measurements revealed a six-coordinate local symmetry around the Cr(III) ions which depicted that the complexes were paramagnetic with magnetic moment values ranging from 5.10 to 6.00 BM. Powder XRD studies confirmed that the amino acid complexes were crystalline with monoclinic crystal structure. The in vitro biological activity of the investigated chromium(III) complexes with alanine and valine was tested against Bacillus subtilis, Staphylococcus aureus, Salmonella typhi, Pseudomonas aeruginosa, and Escherichia coli. All the microorganisms were standardized using 0.5 McFarland standard. The antimicrobial studies showed that the ligands were biologically active with an inhibition zone range of 10-17 mm and their metal complexes showed significantly enhanced antimicrobial sensitivity with an inhibition zone range of 12-21 mm. The standard drug showed slightly better activity with an inhibition zone range of 24-38 mm.